As repercussões do ruído ocupacional na audição dos cirurgiões dentistas das Unidades de Saúde da Família de João Pessoa-PB - Gambarra, Priscilla Alves Nóbrega (2012)
INTRODUCTION: NIHL (Noise Induced Hearing Loss) is a condition that results from the accumulation of prolonged exposure to noise, causing a slow and progressive hearing impairment, sensorneural, not very deep, but irreversible. The dentist, individuals exposed to noise in their workplace, is susceptible to NIHL. OBJECTIVE: To analyze the auditory and possible risk factors that interfere with the hearing of the dentists from USFs (Unidades de Saúde da Família / Familiar Health Unities) in Joao Pessoa / PB. METHODOLOGY: There were interviews, audiological evaluations, instrumental and environmental noises within 65 dentists from Family Health Units in Joao Pessoa / PB to identify auditory characteristics and risk factors for hearing-surgeons dentists by using proportion measures calculation for categorical variables, and having the Statistical Logistic Regression Method. RESULTS: It was observed that 43.07% of the dentists who were evaluated had lower hearing in, at least, some of the characteristic frequencies of NIHL. It was found that the main ear symptoms cited by these professionals were to have the sensation of hearing loss (55%), and buzzer (50%), and also that the instruments which showed values above the allowed limits were turbine high rotation (61%) and the compressor (55%). The variables considered as risk factors for hearing loss based on logistic regression were: age over 45 years old, working time more than 10 years, a feeling of hearing loss, tinnitus and noise level of the compressor greater than 85 dB. CONCLUSION: The ear symptoms (tinnitus and hearing loss) are presented in a large number of dentists, and the noise emitted by the instruments used by these professionals is often high, presenting some risk factors for Noise Induced Hearing Loss and some of them may be prevented or controlled through specific strategies.